A new species of Odonaspis Leonardi, 1897 (Hemiptera: Coccomorpha: Diaspididae) from China - Chen, Qian; Jian, Qian; Xing, Jichun (Zootaxa, 2024)
A new species of armoured scale insect (Hemiptera: Coccomorpha: Diaspididae: Aspidiotinae: Odonaspidini), Odonaspis renhuaiensis Chen, Jian & Xing sp. nov. is described and illustrated from Guizhou Province, China. The type specimens are deposited at the Institute of Entomology, Guizhou University, Guiyang, China. An identification key based on the morphology of adult females is provided to separate all the species of Odonaspis Leonardi, 1897.